Policy and Legal Analysis on Electronic Information and Transaction Laws - Muhammad Andi Septiadi (UIN Sunan Gunung Djati, 2022)
After the passage of the Information and Electronic Transaction law in Indonesia, there is a policy in the form of certain restrictions on conveying rights and aspirations through social media, of course highlighting the problem of hate speech. The purpose of this research is to add insight and application of the ITE Law in solving various problems ranging from hate speech to hate speech on social media. The method used in conducting research is the research method of Inductive qualitative data analysis techniques. This technique is used because it is considered to be able to support and assist us in facilitating the search for data and facts because this method is based on the data obtained and the ITE Law also requires many respondents so that the results of the research do not favor one party. The results of this study can be a reference whether the ITE Law is in line with the 1945 Constitution as a source of law in force in Indonesia. However, in practice there are still multiple interpretations of articles such as 27, 28 and 29 of the ITE Law. This article seems to be a scary thing for critics who are active on social media, or it can be misused as a tool to silence the truth and a political weapon, because there are still some powerful individuals who use this for personal gain. Our suggestion is that the government can review and revise the articles which still have multiple interpretations so that the possibility of having a negative connotation, and the community's stigma towards UU ITE itself can change.